Processing of Virgin Coconut Oil in Sri Lanka Using Cold Extraction Method: An Economic Analysis - P. M. E. K. Pathiraja; M. T. N. Fernando; J. M. M. A. Jayasundera (International Coconut Community Journal, 2008)
Virgin Coconut Oil (VCO) is a newly introduced product in Sri Lanka with a high export market potential. Only a few entrepreneurs however, are capitalizing on this opportunity due to several factors such as lack of rigorous economic analyses and unavailability of information on export market opportunities. Against this background, this study attempts to analyse the economic viability of this enterprise in Sri Lanka. Interestingly, it was found that the VCO provides the highest net return per 1000 coconuts utilized compared to the other traditional coconut kernel products. The pay-back period for the initial investment on machineries was little over a month under current prices of inputs and outputs. Sensitivity analysis suggests that the crucial factor that determines the economic viability of this enterprise is world market VCO price and the sensitivity of the net return of VCO production for the nut price is very low. The break-even price of one liter of VCO was found to be US $ 4.8 whereas it receives US $ 8 in the export market. This study concluded the need of encouraging VCO production in Sri Lanka, given the long-term brighter outlook of the global VCO industry.